MENINGKATKAN KEMAMPUAN MENGENAL BAGIAN TUMBUHAN MELALUI MEDIA SCRATCH BAGI ANAK TUNADAKSA - Putri, Nabila Amelia; Nurhastuti, Nurhastuti; Ardisal, Ardisal; Efrina, Elsa (Universitas Muhammadiyah Ponorogo, 2024)
This research was motivated by problems that researchers encountered when carrying out field practice (PL) at SLB Negeri 1 Pagaruyung regarding learning for physically disabled children in class IV in the science and science subject about recognizing plant parts, where the teacher only used makeshift media such as a blackboard and pictures. The aim of this research is to improve the ability to recognize plant parts for children with physical impairments through scratch media. This research uses qualitative and quantitative methods with two cycles and each cycle has four meetings. In the first cycle, children with the initial S received scores of 12%, 31%, 43% and 62%. In cycle II, children with the initial S got scores of 87%, 87%, 100% and 100%. Data analysis shows that the use of scratch media can improve children's ability to recognize plant parts